用于改善新无线电（NR）定位性能的技术 (2025)
本申请涉及用于改善新无线电(NR)定位性能的技术。本文公开了用于确定无线设备的位置的系统、方法和电路。在一个实施例中，提供了一种用于包括基带电路的第一无线通信设备的装置，该基带电路具有被配置为发射和接收射频(RF)信号的RF接口。该装置包括一个或多个处理器，该一个或多个处理器被配置为：处理从第二无线通信设备接收的信号以标识该第一无线通信设备和该第二无线通信设备之间的至少第一到达路径和另一到达路径；以及基于该第一到达路径和该另一到达路径来确定该第二无线通信设备的位置。 Systems, methods, and circuitries are disclosed for determining a position of a wireless device. In one example, an apparatus for a first wireless communication device including baseband circuitry having a radio frequency (RF) interface configured to transmit and receive RF signals is provided. The apparatus includes one or more processors configured to process a signal received from a second wireless communication device to identify at least first arrival path and a different arrival path between the first wireless communication device and the second wireless communication device; and determine a location of the second wireless communication device based on the first arrival path and the different arrival path.